2013
DOI: 10.1002/marc.201200741
|View full text |Cite
|
Sign up to set email alerts
|

The Pt‐Organometallic Version of Perigraniline: Going Blue

Abstract: Four conjugated push-pull organometallic polymers ([Pt]-AQ)n ([Pt] = trans-bis(phenylacetylene)bis(tributylphosphine)platinum(II); AQ = 2-bromo-, 2,6-dibromo-, 2,6-diamino-, and unsubstituted anthraquinone diimine) were prepared and characterized by UV-vis spectroscopy and electrochemistry. A low-energy charge transfer, CT, band ([Pt]*→AQ; confirmed by density functional theory calculations), was found in the 445-500 nm window rather than the expected red-shifted range above 630 nm. X-ray structures of four mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
2
16
1
Order By: Relevance
“…Recently, the strategy to increase the efficiency of bulk heterojunction solar cells based on conjugated polymer was set on «(push–pull) n » structures . In this respect, our group used appropriately substituted quinonediimines ( QN 2 ) and anthraquinone diimines ( AQN 2 ) as tunable electron acceptors connected to trans ‐bis(ethynyl)bis‐(phosphine)platinum(II) as an electron‐rich unit, [Pt] , for the «(push–pull) n » design, and the photophysical properties of these tailored polymers ( P1a–e , P2a–c , P3 ; Scheme ) were thoroughly investigated . In all cases, the absorption spectra are characterized by a broad low‐energy charge transfer (CT) band arising from [Pt] → QN 2 or [Pt] → AQN 2 , which is highly sensitive to substitution and the structure of the acceptor, and higher energy π–π* features centered on the [Pt] chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the strategy to increase the efficiency of bulk heterojunction solar cells based on conjugated polymer was set on «(push–pull) n » structures . In this respect, our group used appropriately substituted quinonediimines ( QN 2 ) and anthraquinone diimines ( AQN 2 ) as tunable electron acceptors connected to trans ‐bis(ethynyl)bis‐(phosphine)platinum(II) as an electron‐rich unit, [Pt] , for the «(push–pull) n » design, and the photophysical properties of these tailored polymers ( P1a–e , P2a–c , P3 ; Scheme ) were thoroughly investigated . In all cases, the absorption spectra are characterized by a broad low‐energy charge transfer (CT) band arising from [Pt] → QN 2 or [Pt] → AQN 2 , which is highly sensitive to substitution and the structure of the acceptor, and higher energy π–π* features centered on the [Pt] chromophore.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the pyrolysis temperature while other parameters remain constant increases the micropore volume [70]. Plasma pretreatment of PET with a microwave apparatus prior to carbonization showed positive results, which could help reduce the need for a subsequent activation step [71]. The use of these carbons as electrode material in supercapacitors has also been investigated by the group of researchers [72].…”
Section: Chemical Activationmentioning
confidence: 99%
“…Choi et al [69] reported a self-controlled synthesis of hb-PAEKs from diphenyl ether (or 1,4-diphenoxybenene, B 2 ) and trimesic acid (A 3 ) via the Friedel-Crafts reaction. Baek and coworkers developed optimized conditions for Friedel-Crafts acylation in poly(phosphoric acid)/phosphorus pentoxide (PPA/P 2 O 5 ) medium for the preparation of hb-PAEKs [70,71]. Martinez and Hay [72,73] proposed the efficient synthesis and characterization of hb poly(aryl ether sulfone)s with a K 2 CO 3 /Mg(OH) 2 catalyst system for nucleophilic aromatic substitution.…”
Section: Synthesis Of Aromatic Hyperbranched Polymersmentioning
confidence: 99%
See 2 more Smart Citations